Students' attitude towards online learning amid Covid-19 pandemic / Siti Hajar Khalid and Nor Aimi Abdul Wahab - Khalid, Siti Hajar; Abdul Wahab, Nor Aimi (Universiti Teknologi MARA, 2021)
The Coronavirus 2019 (COVID-19) outbreak has resulted in most colleges being forced to select Open Distance Learning (ODL). Many students have faced various challenges throughout their studies due to the rapid shift from conventional learning to ODL. Thus, this study aims to investigate students' attitudes and challenges towards ODL for university courses amid the COVID-19 pandemic. A questionnaire was distributed online to Electrical Engineering diploma students (N=60) based on 11 close-ended questions on student attitude towards ODL. Findings revealed that 70% of the students felt a significant disparity between traditional learning and ODL, with the benefits of traditional classroom learning outweighing ODL. 80% of the respondents stated that as opposed to online learning, traditional learning in the classroom was more inspiring. Among the critical issues students faced were lack of internet connection, technical and money-related constraints, difficulty in engaging virtual communication with the instructor, lack in reaction time, and the absence of the socialisation element as in face-to-face classroom. Improvements on the ODL method need to be carried out continuously to enhance students' attitude towards ODL.